Design and construction of a one person hybrid vehicle, for cities with extreme weather and topographic conditions (AACINI - International Journal of Industrial Engineering, 2024)
Ushuaia city offers adverse conditions for the use of bicycles as a means of transport. In a recent survey, out of a total of 158 respondents, only 5 (3.2%) use a bicycle and do not use a car. The main reasons for not cycling are the weather (very low temperatures, strong winds, rain, snow, ice) and the topography (streets with steep slopes). In this context, and with funds granted by the PFI 2021 program (COFECyT - Federal Innovation Projects), a group of research professors and students of Industrial Engineering and Systems Analysis of the UNTDF AIAS are building a prototype of a hybrid vehicle for one person, with a passenger compartment, two electrically driven front wheels and a back wheel driven by pedaling, which can be widely used in our region, reducing environmental pollution and promoting the user's controlled physical activity. In this way, the aim is to fill the gap that is covered by the bicycle in other cities. Simultaneously, and with the aim of integrating investigation, academic background, professional development and bonding with our community, three Industrial Engineering students are working on an investment project and a business plan for the construction and small-scale commercialization of this vehicle, as part of their degree thesis. In this work, we describe: the establishment of the network that enabled the realization of the project; the main components and technical characteristics of the prototype; and the technology transfer process to the community, once the prototype has been constructed and tested.
Keywords: hybrid tricycle; all-wheel-drive; prototype; extreme conditions; sustainable mobility